1999
DOI: 10.4141/a98-106
|View full text |Cite
|
Sign up to set email alerts
|

Degradability and digestibility of full-fat soybeans treated with different sugar and heat combinations

Abstract: R. 1999. Degradability and digestibility of full-fat soybeans treated with different sugar and heat combinations. Can. J. Anim. Sci. 79: 213-220. Two experiments were conducted to study the effects of different combinations of sugars and heating time and temperature on the ruminal undegradable protein fraction and DM digestibility of full-fat soybeans. In the first experiment, the influence of sugar addition before heating (none, soaked in either a high fructose corn syrup [HFCS] solution, lignosulfonate or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
19
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 22 publications
7
19
1
Order By: Relevance
“…Micronization is known to decrease CP degradation rate of full fat soybeans treated at 110°C for 0.5 h (Petit et al 1999) and full fat canola seed heated at 110 to 115°C for 90 s (Wang et al 1997). Moreover, our results agree with the findings of Hsu and Satter (1995), who reported that RUP increased with increased time of heating and temperature.…”
Section: Methodssupporting
confidence: 90%
See 3 more Smart Citations
“…Micronization is known to decrease CP degradation rate of full fat soybeans treated at 110°C for 0.5 h (Petit et al 1999) and full fat canola seed heated at 110 to 115°C for 90 s (Wang et al 1997). Moreover, our results agree with the findings of Hsu and Satter (1995), who reported that RUP increased with increased time of heating and temperature.…”
Section: Methodssupporting
confidence: 90%
“…In general, micronization effects were greater with more intense heat treatments as previously reported by Mosimanyana and Mowat (1992) and Petit et al (1999) for full fat soybeans. Micronization is known to decrease CP degradation rate of full fat soybeans treated at 110°C for 0.5 h (Petit et al 1999) and full fat canola seed heated at 110 to 115°C for 90 s (Wang et al 1997).…”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…As a result, heating temperature had a greater effect on the RUP of roasted soybeans (Table 4). Petit et al (1999;2002) reported similar findings.…”
Section: Discussionsupporting
confidence: 61%